2020
DOI: 10.3390/buildings10040063
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Steel Structure-Foundation Systems Designed According to Eurocode 8 Provisions: The Case of Near-Fault Seismic Motions

Abstract: The seismic performance of steel structure-foundation systems subjected to near-fault earthquakes was assessed on the basis of response results from nonlinear time-history seismic analyses. The structural results included the maximum values for residual interstory drift ratios, base shears, and overturning moments of the steel structures, as well as the maximum values for residual settlement and tilting of the foundations. In order to reveal the influence of soil-building-interaction on the aforementioned resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…It is recalled that Eurocode 8 [2], in its current version, does not provide a specific methodology for the analysis and design of steel building-foundation systems, considering or neglecting SSI, in regions where the potential seismic hazard from long duration seismic motions is high or even dominates. A similar deficiency in Eurocode 8 [2] has been pointed out by Katsimpini et al [29] for the case of near-fault seismic motions.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…It is recalled that Eurocode 8 [2], in its current version, does not provide a specific methodology for the analysis and design of steel building-foundation systems, considering or neglecting SSI, in regions where the potential seismic hazard from long duration seismic motions is high or even dominates. A similar deficiency in Eurocode 8 [2] has been pointed out by Katsimpini et al [29] for the case of near-fault seismic motions.…”
Section: Introductionsupporting
confidence: 58%
“…The results of this work are deemed to be realistic and can be viewed, even for comparison purposes, in conjunction with those obtained by Katsimpini et al [29] for the case of near-fault seismic motions. It is recalled that Eurocode 8 [2], in its current version, does not provide a specific methodology for the analysis and design of steel building-foundation systems, considering or neglecting SSI, in regions where the potential seismic hazard from long duration seismic motions is high or even dominates.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In these models, the soil-structure interaction (SSI) effect is neglected. However, many studies have indicated that a system of the steel building-foundation should be taken into account, especially ones subjected to near-source earthquakes [18]. An input, the values of mass and stiffness of each floor are assumed to be the same, given as: m i = 0.0714 kNs 2 /mm and k i = 100 kN/mm.…”
Section: Description Of Case Study and Ground Motion Inputsmentioning
confidence: 99%
“…Ground motions can be divided into near-fault and far-fault ground motions, depending on the distance from the epicenter and the characteristics of each ground motion. Recent studies have analyzed the effects of near-fault ground motion on architectural and civil structures, such as nuclear power plants, dams, bridges, and buildings [11][12][13][14]. Near-fault ground motion generally shows strong and narrow-band pulses for a short period in spectral accelerations [15][16][17].…”
Section: Introductionmentioning
confidence: 99%